PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES PESERTA DIDIK KELAS VIII.6 SMP NEGERI 43 PALEMBANG - Desfianti Desfianti (JS (JURNAL SEKOLAH), 2020)
Abstract.Increasing English Learning Outcomes Through Learning Models Examples Non Examples Class VIII.6 Students of SMP Negeri 43 Palembang. The fundamental problem in this study is that most of the students in grade VIII.6 at SMP Negeri 43 Palembang do not understand the material for giving instructions, inviting, prohibiting, asking for permission, and how to respond. Starting from the description above, the problem in this study is formulated, namely the formulation of the problem in this study is: "How is the improvement of English learning outcomes through the learning model Examples non Examples students class VIII.6 SMP Negeri 43 Palembang?". The expected objective of this study was to determine the improvement of English learning outcomes through the application of the Examples non Examples learning model for class VIII.6 students of SMP Negeri 43 Palembang. The subjects in this study were students of class VIII.6 SMP Negeri 43 Palembang, totaling 32 students. This research will be carried out in the even semester of the 2018/2019 academic year in February to April 2019. This classroom action research has been said to be complete with the evidence of an increase in English learning outcomes using the Examples non Examples learning model. Keywords: Learning Outcomes, English, Examples non Examples Abstrak.Peningkatan Hasil Belajar Bahasa Inggris Melalui Model Pembelajaran Examples Non Examples Peserta Didik Kelas VIII.6 SMP Negeri 43 Palembang. Permasalahan mendasar dalam penelitian ini adalah sebagian besar peserta didik kelas VIII.6 SMP Negeri 43 Palembang kurang memahami tentang materi ungkapan memberi instruksi, mengajak, melarang, minta ijin, serta cara responnya. Bertitik tolak dari uraian di atas, maka dirumuskan masalah dalam penelitian ini yaitu yang menjadi rumusan masalah dalam penelitian ini adalah: “Bagaimanakah Peningkatan hasil belajar Bahasa Inggris melalui model pembelajaran Examples non Examples  peserta didik kelas VIII.6 SMP Negeri 43 Palembang?”. Tujuan yang diharapkan dari penelitian ini adalah untuk mengetahui peningkatkan hasil belajar Bahasa Inggris melalui penerapan model pembelajaran Examples non Examples peserta didik kelas VIII.6 SMP Negeri 43 Palembang. Subjek dalam penelitian ini adalah peserta didik kelas VIII.6  SMP Negeri 43 Palembang yang berjumlah 32 peserta didik. Penelitian ini akan dilaksanakan pada semester genap tahun ajaran 2018/2019 pada bulan Februari s/d April tahun 2019. Penelitian tindakan kelas ini telah dikatakan tuntas dengan dibuktikannya peningkatan hasil belajar Bahasa Inggris menggunakan model pembelajaran Examples non Examples.  Kata Kunci: Hasil Belajar,Bahasa Inggris, Examples non Examples